2004
DOI: 10.1096/fj.02-1202fje
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐2 (MMP‐2) is present in the nucleus of cardiac myocytes and is capable of cleaving poly (ADP‐ribose) polymerase (PARP) in vitro

Abstract: Matrix metalloproteinases (MMPs) are traditionally known for their role in extracellular matrix remodeling. Increasing evidence reveals several alternative substrates and novel biological roles for these proteases. Recent evidence showed the intracellular localization of MMP-2 within cardiac myocytes, colocalized with troponin I within myofilaments. Here we investigated the presence of MMP-2 in the nucleus of cardiac myocytes using both immunogold electron microscopy and biochemical assays with nuclear extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
218
1
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(243 citation statements)
references
References 37 publications
9
218
1
11
Order By: Relevance
“…Intracellular existence of matrix metalloproteinase and its activation under various conditions have been reported (23,32,33). In the previous study, we demonstrated that MMP3 is activated in DA cells treated with 1-methyl-4-phenylpyridinium, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-mediated DA neuronal degeneration in the mouse SN was largely attenuated in Mmp3 null mice (22).…”
Section: Discussionmentioning
confidence: 80%
“…Intracellular existence of matrix metalloproteinase and its activation under various conditions have been reported (23,32,33). In the previous study, we demonstrated that MMP3 is activated in DA cells treated with 1-methyl-4-phenylpyridinium, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-mediated DA neuronal degeneration in the mouse SN was largely attenuated in Mmp3 null mice (22).…”
Section: Discussionmentioning
confidence: 80%
“…Poly (ADP-ribose) polymerase (PARP) yes (Kwan et al, 2004) Pregnancy zone protein yes yes (Arbelaez et al, 1997) Pro-IL-1β yes yes (Schonbeck et al, 1998) Pro-IL-8 yes…”
Section: (Van Den Steen Et Al 2000)mentioning
confidence: 99%
“…An interesting observation is that TIMP-1, in addition to the extracellular milieu, can also be found in the nucleus (Zhao et al, 1998), and may even be specifically translocated there from the cell membrane (Ritter et al, 1999). Recently, also MMP-2 was found to be present in the nucleus, and a pro-apoptotic nuclear protein, poly (ADP-ribose) polymerase was cleaved by MMP-2 in vitro suggesting that MMP-2 could partially substitute for caspases in the apoptotic cascade (Kwan et al, 2004). Fotouhi et al, 1994) CTTHWGFTLC peptide catalytic activity TSRI265 docking of MMP-2 to αVβ3 integrin a note that the lack of other inhibitable targets may indicate that the compound has not been tested for inhibition of other proteinases.…”
Section: Gelatinase Inhibitors Naturally Occuring Gelatinase Inhibitorsmentioning
confidence: 99%
“…Metaloproteínases da matriz extracelular (MMPs) são uma família de endopeptidases zinco-dependentes conhecidas por degradar componentes do tecido conjuntivo em processos fisiológicos e patológicos (Kwan, Schulze et al 2004). As…”
Section: Metaloproteínases Da Matriz Extracelularunclassified
“…As MMPs são responsáveis pela degradação de muitos componentes da ECM, tais como colágeno, caseína, fibronectina, elastina, laminina e proteoglicana (Aimes and Quigley 1995;Kwan, Schulze et al 2004;Page-McCaw, Ewald et al 2007). Elas são descritas em eventos fisiológicos tais como: desenvolvimento embrionário, morfogênese, reprodução, reabsorção e remodelamento tecidual (Gross and Lapiere 1962).…”
Section: Figuraunclassified